PELATIHAN KEWIRAUSAHAAN SOSIAL EKONOMI MELALUI KELOMPOK PEER GROUP DI PERUMAHAN NASIONAL EMPAT KOTA JAYAPURA - Lobo, Albertina Nasri; Abidjulu, Fitrine Christiane (JURNAL PENGABDIAN PAPUA, 2024)
Social Economic Entrepreneurship Training through peer group is an approach for teenagers in the same age. The aim of this training is to provide a knowledge and a skill utilizing social media to promote many things such as various social problems and economic creative activities. Moreover, this training is conducted with dividing the participants into two groups based on level of education and age. For the delivery the substance, uses demonstrative method, discussion, and teaching while for evaluating the training, pre-test and post-test are used. This evaluation is important to make sure that the participants grab all the knowledge and skill from the training: the peer group is having the ability to utilize electronic media, social media, and Canva application to design. The result of this training shows that the teenagers are enthusiastic about the benefit and the sustainability of their business in the near future. Social Economic Entrepreneurship Training is extremely important for all teenagers since social entrepreneurial. This training concludes that there is an increase of knowledge, skills, interest, and motivation of teenagers in their social group about social and economy entrepreneurship. Furthermore, it is necessary to build a collaboration and a commitment between business sector and education sector that seriously concern of developing teenagers’ group in social and economic entrepreneurship.